Effectiveness of Nurse Navigated Self-Management Strategies on Knowledge, Skill and Respiratory Parameters Regarding Management of Chronic Obstructive Pulmonary Diseases Among Patients Attending Outpatient Department in Selected Hospital - Gunasekaran, Malathi; Sathiyalatha, Sarathi; Hemavathy, V. (British Journal of Healthcare and Medical Research, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a lung disease characterized by chronic obstruction of lung airflow that interferes with normal breathing and is not fully reversible. Aim and Objective: To assess the effectiveness of Nurse Navigated Self-Management Strategies on knowledge, skill and respiratory parameters regarding management of COPD among patients attending OPD. Methodology: Quantitative research approach, Quasi Experimental-Pretest post-test with non-equivalent control group design, was adopted to assess effectiveness of Nurse Navigated Self-Management Strategies (NNSMS) on knowledge, skill and respiratory parameters regarding management of Chronic Obstructive Pulmonary Diseases (CORD) among 300 COPD patients (150 samples in each experimental and control group) attending outpatient department (OPD) at selected hospital. COPD patients who fulfilled the inclusion and exclusion criteria, using Non probability purposive sampling technique was used to select the samples in this study. Nurse Navigated Self-Management Strategies (NNSMS) was administered and the level of knowledge, skill and respiratory parameters and compared with the pre and post-test level between experimental and control group. Results: The study findings revealed that the pretest knowledge score was 10.93 with SD 1.31 and the post-test knowledge score was 19.47 with SD 1.98 and the skill score of pretest was 5.10 with SD 1.86 and post test score was 11.37 with SD 2.70 .The respiratory parameters pretest score was 8.30 with SD 2.18 and posttest Mean score was 5.87 with SD 2.36. The calculated’ Paired t-test’ value (18.89,3.77 and 17.47) for knowledge skill and respiratory parameters, respectively. There was very high statistical significance was found in the experimental group at the level p<0.001. Conclusion: The results revealed that the Nurse Navigated Self-Management Strategies (NNSMS) on knowledge, skill and respiratory parameters was effective in improving the knowledge and skill, and reducing the respiratory parameters regarding management of Chronic Obstructive Pulmonary Diseases. It can be utilized for the home management of patients with COPD and other respiratory diseases. Keywords: Chronic Obstructive Pulmonary Diseases. Nurse Navigated Self-Management Strategies knowledge, skill and respiratory parameters.